Special issue: Proceedings of the 15th ISIC - The Information Behaviour Conference, Aalborg, Denmark, August 26-29, 2024 (Information Research: An International Electronic Journal)
‘It never seems to stop’ Six high school students’ experiences of information overload Mira Grønning Aadland, Jannica Heinström